Will video kill the radio star? Digitalisation and the future of banking - Thorsten Beck; Stephen G. Cecchetti; Magdalena Grothe; Malcolm H. D. Kemp; Loriana Pelizzon; Antonio Sánchez Serrano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
The contribution of financial and non-financial risks to the overall level of risk in the system depends on the current state of the EU banking system (which, in the aggregate and compared with banking sectors in other major advanced economies, cannot be characterised as strong) and how incumbent banks interact with fintechs and big techs in the future, an area still dominated by uncertainty. Consequently, this report uses three alternative scenarios for the EU financial system in 2030 as a basis for discussing the appropriate macroprudential policy responses.
Keywords: 330; financial system; bank; financial service; digitalization; financial product; financial technology; financial risk; EU countries; Finanzsystem; Bank; Finanzdienstleistung; Digitalisierung; Finanzprodukt; Finanztechnologie; Finanzrisiko; EU-Staaten